Unveiling midcrustal seismic activity at the front of the Bolivian altiplano, Cochabamba region - Gonzalo Antonio Fernandez M; Benoit Derode; Laurent Bollinger; Bertrand Delouis; Mayra Nieto; Felipe Condori; Nathan Sarret; Jean Letort; Stephanie Godey; Mathilde Wimez; Teddy Griffiths; Walter Arce (Seismica, 2025)
Located in the heart of the Bolivian orocline, the Cochabamba department and its two million inhabitants are exposed to frequent seismic activity. However, the tectonic structures causing these earthquakes remain poorly identified. Indeed, Bolivia’s national seismological network does not optimally cover the area and the hypocentral locations of local earthquakes are therefore subject to large uncertainties which hinder their association with specific faults. We established a regional network consisting of 11 broadband and short-period seismic stations, spaced approximately 20 km apart. This study highlights the initial 6-month seismic bulletin made by manual and automated deep-neural-network based seismic phase picking. We also test the network's ability to resolve focal mechanisms of moderate to small events with a combined inversion of waveforms and polarities. Our preliminary results document midcrustal microseismicity located in the Main Thrust fault shear zone, and in its hangingwall, in a region affected by tectonic slivers and transverse faults impacting the sedimentary cover. These outcomes provide fresh insights into the fault system’s seismogenic behavior and potential across the Bolivian orocline.